Klimawandel in Österreich - Die letzten 20.000 Jahre ... und ein Blick voraus. - Schmidt, Roland (alpine space - man and environment, 2009)
The changes in climate affected especially the Alps during the past 20,000 years. In this book more than 20 experts from different fields present the current state of climate research in Austria, starting from the last ice age until the current climate warming. In the early Holocene human activities were driven by the climate while in modern societies climate change is driven to an increasing amount by human activities. Undoubtedly the Alps where much more affected by climate change than many other regions of the world, but still the authors dare to look ahead into the future.